Harvesting Chaetoceros gracilis by flocculation using Chitosan - W Yamin; Sitti Raehanah Muhamad Shaleh; Ching Fui Fui @ Faihana Ching Abdullah; Rafidah Binti Othman; Bernardette Mabel Manjaji Matsumoto; Saleem Mustafa; S Shigeharu; G Kandasamy (IOP Publishing Ltd, 2019)
Flocculation is a method of harvesting microalgae by separating cells from the culture medium using flocculating agents. Ferric Chloride and alum are conventional flocculants that have the disadvantages of toxic residue. In this study, chitosan, a non-toxic flocculating agent is tested on Chaetoceros gracilis to determine the effect of culture conditions (salinity and cell density) towards the flocculation efficiency (FE). Marine diatom C. gracilis is cultured using Walne’s Media for 8 days in a temperature-controlled room and illuminated for 12 hours. Four different salinities (20, 25, 30, 35 ppt), four different cell densities (0.5, 2, 4, 6 x 10 6 cells mL -1), and six chitosan concentration (0, 15, 30, 45, 60, 75 ppm) are the parameters tested in this study. Measuring cylinder test is used to measure FE using spectrophotometer (OD750). From the results, salinity and cell density affect significantly the FE of the diatom. In 20 ppt culture, the FE was 89% after 50 minutes using 75 ppm of chitosan at a density of 4 x 10 6 cells mL-1 . Growth conditions of the diatom culture have strong influences on the flocculation performances. The chitosan can be an option for non-toxic flocculants for concentrating live feeds in the aquaculture industry.